Eliminating Boundary Layer Separation on a Cylinder with Nonuniform Suction - James Ramsay; Mathieu Sellier; Wei Hua Ho (International Journal of Aerospace Engineering)
Boundary layer separation negatively influences the performance of aerospace vehicles, for example, by triggering static stall or reducing combustion engine efficiency. Developing effective flow control to delay or eliminate separation is therefore of real use to the field. In this paper, numerical studies were carried out to optimise distributed suction profiles for preventing boundary layer separation on a circular cylinder in the fully laminar regime (Re<188), with the least control effort. Relationships were found between the Reynolds number, the separation angle of the uncontrolled case, and the uniform suction needed to eliminate separation. It was found that for Re>20, the uniform suction required to eliminate separation followed a quadratic profile, as a function of Re. Maximum uniform suction effort was needed at Re=20, requiring a suction coefficient of CQ=49.14 (as a percentage of the free-stream velocity) to eliminate separation. To resolve the best nonuniform suction profile at Re=180, a variety of optimisation studies were performed using the coordinate search method. It was determined that the use of six control segments on each half of the cylinder provided the best control and efficient convergence to the optimal solution. 6-segment nonuniform suction eliminated separation at Re=180 with net suction effort of CQ=13.26 compared to CQ=31.25 for the uniform case. These optimal suction profiles were compared using time-dependent simulations to confirm that both methods eliminate separation when introduced to an already unsteady case. Nonuniform suction eliminated separation faster, though uniform suction was more stable.